IRE1α Expedites the Progression of Castration-Resistant Prostate Cancers via the Positive Feedback Loop of IRE1α/IL-6/AR - Yang, Fan; Yuan, Chong; Wu, Dan; Zhang, Jing; Zhou, Xingchun (Frontiers in Oncology, 2021)
CCastration-resistant prostate cancer (CRPC) is the lethal form of prostate cancer (PCa), and the underlying molecular mechanism has not been fully elucidated. Inositol requiring enzyme 1 alpha (IRE1α), a key regulator of unfolded protein response (UPR), is intimately associated with PCa progression. However, whether IRE1α is implicated in CRPC development remains unknown. Here, we showed that IRE1α expression was significantly increased in CRPC tissues and high-grade PCa tissues. Overexpression of IRE1α promoted PCa cell proliferation under the androgen deficiency condition in vitro and in vivo. Mechanistically, increased IRE1α expression induced IL-6 secretion via the IRE1α/XBP-1s signal pathway. IRE1α-induced IL-6 activated androgen receptor (AR), and the activation of AR by IL-6, in turn, promoted IRE1α expression. IRE1α formed a positive feedback loop with IL-6 and AR to promote prostate cancer cell proliferation under the androgen-deficient condition. In clinical PCa samples, high IRE1α expression correlated with elevated IL-6 and increased PSA expression. Our findings demonstrated a novel mechanism of CRPC progression and suggest targeting IRE1α may be a potential target for the prevention and treatment of CRPC.